2004
DOI: 10.1021/ac0489824
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Multiphoton Dissociation of O-Linked Mucin-Type Oligosaccharides

Abstract: Oligosaccharides are known to play important roles in many biological processes. In the study of oligosaccharides, collision-induced dissociation (CID) is the most common dissociation method to elucidate the sequence and connectivity. However, a disadvantage of CID is the decrease in both the degree and efficiency of dissociation with increasing mass. In the present study, we have successfully performed infrared multiphoton dissociation (IRMPD) on 39 O-linked mucin-type oligosaccharide alditols (both neutral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 56 publications
3
94
0
Order By: Relevance
“…Several lower molecular weight glycosidic and cross-ring cleavage product ions were observed only following IRMPD. Although IRMPD and lowenergy CAD are both low-energy vibrational excitation techniques, Lebrilla and coworkers have shown that the fragmentation efficiency in IRMPD is greater than that in CAD for larger oligosaccharides [56]. An alternative explanation for the absence of low molecular weight species following CAD is the time-of-flight effect when transferring ions from the external hexapole to the ICR cell.…”
Section: Ms/ms Of Neutral Oligosaccharidesmentioning
confidence: 99%
“…Several lower molecular weight glycosidic and cross-ring cleavage product ions were observed only following IRMPD. Although IRMPD and lowenergy CAD are both low-energy vibrational excitation techniques, Lebrilla and coworkers have shown that the fragmentation efficiency in IRMPD is greater than that in CAD for larger oligosaccharides [56]. An alternative explanation for the absence of low molecular weight species following CAD is the time-of-flight effect when transferring ions from the external hexapole to the ICR cell.…”
Section: Ms/ms Of Neutral Oligosaccharidesmentioning
confidence: 99%
“…Alternatively, other activation techniques have been used for the structural characterization of glycans, including infrared multiphoton dissociation (IRMPD) [40 -43] and electron capture dissociation (ECD) [44,45]. Although IRMPD and CID are both low-energy vibrational excitation techniques, Lebrilla and coworkers [42] have shown that the fragmentation efficiency of IRMPD increases with increasing oligosaccharide size. Recent efforts in the fragmentation of various metal-cationized oligosaccharides by ECD have provided structural information complementary to IRMPD [45].…”
mentioning
confidence: 99%
“…As the low-energy CID in the IT analyzers [32,34,44] or the PSD in MALDI/TOF MS instruments [45] is generally insufficient to accomplish this fragmentation task, we have chosen a MALDI/TOF/TOF MS with high-energy CID capabilities to furnish extensive fragmentation of model neutral [46][47][48][49][50] and acidic [46,51] glycans. An alternative approach pursued elsewhere for extensive fragmentation of glycans involves Fourier transform ion cyclotron resonance MS used in conjunction with sustained offresonance irradiation (SORI) [52], CID [52,53], IR multiphoton dissociation (IRMPD) [54][55][56], or electron capture dissociation (ECD) [54,55]. In our MALDI/TOF/TOF MS experiments, we were able to distinguish a subtle form of isomerism in the mannose-rich glycans [47] (Fig.…”
Section: Capillary Lc/maldi/tof/tof Ms: a Platform For Functional-glymentioning
confidence: 92%